Quantitative investigation of physical and mechanical properties of different artificial aggregate - Mokhatar, ShahrulNiza; Hadipramana, Josef; Ibrahim, Shahiran Liyana; Kamarudin, Ahmad Fahmy (Penerbit UTHM, 2020)
Concrete is an important construction element because it is plastic and soft when newly mixed, yet strong and tough when hardened. However, when the world technologies are develop year by years, lightweight concrete has been commonly used in several structural element applications and its exploitation increases every year on a global basis [1]. Thus, where lightweight concrete is desirable, raising the need for partial or total replacement of the aggregate with a lighter substitute is needed. Lightweight concrete contains artificial aggregate that is natural or synthetic which weighs less than 1100 kg/m3. Due to the low density of Light Weight Aggregate (LWA), it provides better insulation property and can be used to produce light weight concrete. During this period, various types of aggregates have been used.